Brain Connectivity Patterns Dissociate Action of Specific Acupressure Treatments in Fatigued Breast Cancer Survivors - Harris, Richard E.; Ichesco, Eric; Cummiford, Chelsea; Hampson, Johnson P.; Chenevert, Thomas L.; Basu, Neil; Zick, Suzanna M. (Frontiers in Neurology, 2017)
Persistent fatigue is a pernicious symptom in many cancer survivors. Existing treatments are limited or ineffective, and often lack any underlying biologic rationale. Acupressure is emerging as a promising new intervention for persistent cancer related fatigue; however, the underlying mechanisms of action are unknown. Our previous investigations suggested that fatigued breast cancer survivors have alterations in brain neurochemistry within the posterior insula and disturbed functional connectivity to the default mode network (DMN), as compared to non-fatigued breast cancer survivors. Here we investigated if insula and DMN connectivity were modulated by self-administered acupressure by randomizing breast cancer survivors (n=19) to two distinct treatments: relaxing acupressure or stimulating acupressure. All participants underwent proton magnetic resonance spectroscopy of the posterior insula and functional connectivity magnetic resonance imaging at baseline and immediately following 6 weeks of acupressure self-treatment. As compared to baseline measures, relaxing acupressure decreased posterior insula to dorsolateral prefrontal cortex connectivity whereas stimulating acupressure enhanced this connectivity (p<0.05 corrected). For relaxing but not stimulating acupressure, reduced connectivity was associated with sleep improvement. In addition, connectivity of the DMN to the superior colliculus was increased with relaxing acupressure and decreased with stimulating acupressure, whereas DMN connectivity to the bilateral pulvinar was increased with stimulating and decreased with relaxing acupressure (p<0.05 corrected). These data suggest that self-administered acupressure at different acupoints has specificity in relation to their mechanisms of action in fatigued breast cancer survivors.